x^2-2x-8=0

x^2-14x-3=0

x^2-2x-8=0

x^2-14x-3=0

Tutors, please sign in to answer this question.

Inglewood, CA

X^2 - 2X - 8 = 0

a = 1 b = -2 c= -8

put in the form (x+b/2a)^{2 }and keep the balance

(x-2/2)^{2}-1 - 8 =0

(x - 1)^{2}=9

x- 1 = 3 or x -1 = -3

x = 3 + 1 or x = -3 + 1

x = 4, x = -2

previous solution is correct hopefully this explained where the added 1 came from and how to determine what constant to use to keep the balance of the equation.

x^2-14x-3=0

a = 1 b = -14

(x-14/2)^{2 }=x^{2}-14x +49

since you added 49 on the left then add to the right to keep the balance

(x - 7)² =0 + 49 + 3 = 52

x - 7 = √52

x = 7 + √52 or 7 - √52

Woodland Hills, CA

X^2 - 2X - 8 = 0

X^2 -2X **+1 -1** -8 = 0

X^2 - 2X + 1 = 9

( X - 1 ) ^2 = 9

X - 1 = ± √9 = ±3

X = 1 +3 X = 1 - 3

X = -2, 4

You should follow the same procedure and do it yourself.

First step is add +49, -49 to the equation

- Algebra 2 3502
- Algebra 5053
- Math 9839
- Prealgebra 171
- Algebra Word Problem 2481
- Algebra Help 967
- Geometry 1905
- Math Help 5439
- Word Problem 5106
- Precalculus 1574